Astrocytic urea cycle detoxifies A beta-derived ammonia while impairing memory in Alzheimer's disease - Ju, Yeon Ha; Bhalla, Mridula; Hyeon, Seung Jae; Oh, Ju Eun; Yoo, Seonguk; Chae, Uikyu; Kwon, Jea; Koh, Wuhyun; Lim, Jiwoon; Park, Yongmin Mason; Lee, Junghee; Cho, Il-Joo; et al. (Cell Press, 2022)
Alzheimer's disease (AD) is one of the foremost neurodegenerative diseases, characterized by beta-amyloid (A beta) plaques and significant progressive memory loss. In AD, astrocytes are proposed to take up and clear A beta plaques. However, how A beta induces pathogenesis and memory impairment in AD remains elusive. We report that normal astrocytes show non-cyclic urea metabolism, whereas A beta-treated astrocytes show switched-on urea cycle with upregulated enzymes and accumulated entering-metabolite aspartate, starting-substrate ammonia, end-product urea, and side-product putrescine. Gene silencing of astrocytic ornithine decarboxylase-1 (ODC1), facilitating ornithine-to-putrescine conversion, boosts urea cycle and eliminates aberrant putrescine and its toxic byproducts ammonia and H2O2 and its end product GABA to recover from reactive astrogliosis and memory impairment in AD. Our findings implicate that astrocytic urea cycle exerts opposing roles of beneficial A beta detoxification and detrimental memory impairment in AD. We propose ODC1 inhibition as a promising therapeutic strategy for AD to facilitate removal of toxic molecules and prevent memory loss.